Exploration of the Reform Model of “One Outline and Multiple Modules” in Tennis Teaching at Local Normal Universities - Mo, Yi (Journal of Educational Research and Policies, 2025)
With the deepening of higher education reform, tennis teaching in local normal universities is facing challenges such as single content, traditional methods, and one-sided evaluation, which are difficult to meet the requirements of talent cultivation in the new era. The purpose of this study is to explore the application effect of the “one syllabus, multiple modules” reform model in tennis teaching, and provide new ideas for improving teaching quality and cultivating well-rounded talents. The study thoroughly analyzed the basic principles, application advantages, and connection methods with existing courses of the “one syllabus, multiple modules” model. The results show that this model effectively improves students’ learning interest and participation, enhances their comprehensive abilities, and optimizes teaching quality through flexible course settings and personalized teaching. At the same time, this model provides reference for other physical education curriculum reform, promotes the innovation of teaching model, promotes the improvement of evaluation system, and helps teachers’ professional development and teaching ability.